Обнаружение микроспоридий у кровососущих комаров Карелии - Килочицкий, П.Я.; Георгиева, Е.К. (Вестник зоологии, 1982)
An examination of larvae and pupae of seven blood-sucking mosquito species of Northern Karelia showed the presence of Amblyospora microsporidia and other patho-genes in five Aedes species: Ae. cantans M g., Ae. excruricans Walk., Ae, flavescens M u l l., Ae. communis D e g. and Ae. punctor Kirby.